The Effect of Warm Compress and Proper Perineal Support Technique on Prevention of Severe Perineal Trauma - Saima Faraz; Vandana Vasudevan; Huda Manea Ali Ahmed; Daisy Varghese; Nancy Augustine; Ushakumari V. Pillai; Abeer Ammar; Nighat Aftab (Dubai Medical Journal)
Introduction: Vaginal deliveries are frequently linked with genital tract damage, and rips affecting the anal sphincter or mucosa (third- and fourth-degree tears) can cause major complications. To prevent harm, several perineal methods are employed to slow down the delivery of the baby’s head and allow the perineum to extend gently. Midwives all across the globe employ massage, warm compresses, and various perineal care techniques. Objective: The aim of this study was to analyze the effect of warm compress and perineal support on prevention of severe perineal trauma among primiparous women. Design: This study was a quasi-experimental study. Settings: The study settings included tertiary care hospital settings affiliated with the academic center in the UAE. Patients and Methods: Around 192 females were consecutively divided into 2 age-matched groups. Group 1 had 99 patients in which warm perineal compresses were applied in addition to perineal support, and no episiotomy was performed. There were 93 control patients in group 2 who were just given perineal support, and prophylactic episiotomy was performed. Main Outcomes Measured: Maternal risk factors such as an unhealthy perineum and short perineum were noted. The fetal risk factors such as large for gestational age, shoulder dystocia, and occipito-posterior position were also noted. Peripartum data of instrumental delivery, long stage two of delivery, oxytocin augmentation, epidural use, pushing technique, delivery position, and degree of perineal tear were also evaluated. Result: Neither maternal risk factors nor fetal factors were significant between the two groups. However, in peripartum characteristics, instrumental deliveries (17 [18.3%] vs. 0 [0%] p value <0.001) and lithotomy position (53 [57%] vs. 0 [0%] p value <0.001) were significantly more common in the control group. Other risk factors such as oxytocin augmentation, prolonged second stage, and epidural use did not differ significantly between the two groups. Warm compresses prevented severe perineal tears in group 1. Group 1 showed statistically significant (p value <0.001) reduction in severe (grade 2 and 3 tear) form of perineal injury during the second stage of labor. Conclusion: Warm perineal compresses in primigravida females during the second stage of labor may help prevent severe perineal injuries and reduce the incidence of instrumental delivery as well as lithotomy position requirement.